Community of trauma care partnering with stakeholders to improve injury outcomes: focus group analysis - Deborah M Stein; Elliott R Haut; Michelle A Price; Pam J Bixby; Anna Newcomb; Rosemary Kozar; Rochelle Dicker; Princess Fortin; Rachel D Appelbaum; Katherine Joseph; Morgan Hennessy; Sue Prentiss; et al. (Trauma Surgery & Acute Care Open)
Introduction Engaging trauma survivors/caregivers results in research findings that are more relevant to patients’ needs and priorities. Although their perspectives increase research significance, there is a lack of understanding about how best to incorporate their insights. We aimed to capture stakeholder perspectives to ensure research is meaningful, respectful, and relevant to the injured patient and their caregivers.Methods A multiphase, inductive exploratory qualitative study was performed, the first phase of which is described here. Virtual focus groups to elicit stakeholder perspectives and preferences were conducted across 19 trauma centers in the USA during 2022. Discussion topics were chosen to identify patients’ motivation to join research studies, preferences regarding consent, suggestions for increasing diversity and access, and feelings regarding outcomes, efficacy, and exception from informed consent. The focus groups were audio recorded, transcribed, coded, and analyzed to identify the range of perspectives expressed and any common themes that emerged.Results Ten 90-minute focus groups included patients/caregiver (n=21/1) and researchers (n=14). Data analysis identified common themes emerging across groups. The importance of trust and preexisting relationships with the clinical care team were the most common themes across all groups.Conclusion Our findings reveal common themes in preferences, motivations, and best practices to increase patient/caregiver participation in trauma research. The project’s next phases are distribution of a vignette-based survey to establish broad stakeholder consensus; education and dissemination activities to share strategies that increase research engagement and relevance for patients; and the formation of a panel of patients to support future research endeavors.Level of evidence Level IV.